Annealing in Argon Universally Upgrades the Na‐Storage Performance of Mn‐Based Layered Oxide Cathodes by Creating Bulk Oxygen Vacancies. Issue 15 (28th February 2023) - Jin, Junteng; Liu, Yongchang; Zhao, Xudong; Liu, Hui; Deng, Shiqing; Shen, Qiuyu; Hou, Ying; Qi, He; Xing, Xianran; Jiao, Lifang; Chen, Jun
Abstract: Manganese‐rich layered oxide cathodes of sodium‐ion batteries (SIBs) are extremely promising for large‐scale energy storage owing to their high capacities and cost effectiveness, while the Jahn–Teller (J–T) distortion and low operating potential of Mn redox largely hinder their practical applications. Herein, we reveal that annealing in argon rather than conventional air is a universal strategy to comprehensively upgrade the Na‐storage performance of Mn‐based oxide cathodes. Bulk oxygen vacancies are introduced via this method, leading to reduced Mn valence, lowered Mn 3 d‐ orbital energy level, and formation of the new‐concept Mn domains. As a result, the energy density of the model P2‐Na0.75 Mg0.25 Mn0.75 O2 cathode increases by ≈50 % benefiting from the improved specific capacity and operating potential of Mn redox. The Mn domains can disrupt the cooperative J–T distortion, greatly promoting the cycling stability. This exciting finding opens a new avenue towards high‐performance Mn‐based oxide cathodes for SIBs. Abstract : A general approach of annealing in argon atmosphere rather than conventional air is for the first time, demonstrated to comprehensively upgrade the Na‐storage performance (including specific capacity, operating voltage, and cycling durability) of Mn‐based layered oxide cathodes by creating bulk oxygen vacancies.